2020
DOI: 10.1002/car.2653
|View full text |Cite
|
Sign up to set email alerts
|

Safeguarding Children When Fabricated or Induced Illness Is Suspected or Proven: Reviewing the Experiences of Local Safeguarding Children Boards in England

Abstract: ‘The views of representatives from… Local Safeguarding Children Boards (LSCBs) in England were sought on the challenges to safeguarding children from FII’The fabrication or induction of illness (FII) is a relatively rare situation which can lead to serious physical and/or emotional harm to a child. FII is often difficult for professionals to identify and manage. In this study the views of representatives from the 147 Local Safeguarding Children Boards (LSCBs) in England were sought on the challenges to safegua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Last year we published a paper by John Ratcliffe et al . (2020) reviewing the experiences of Local Safeguarding Children Boards in safeguarding children when fabricated or induced illness (FII) is suspected or proven. The authors identified a lot of uncertainty and anxiety on the part of professionals in managing these situations, and a number of challenges faced by Safeguarding Children Boards.…”
Section: Safeguarding Children When Fabricated or Induced Illness Is Suspected Or Provenmentioning
confidence: 99%
“…Last year we published a paper by John Ratcliffe et al . (2020) reviewing the experiences of Local Safeguarding Children Boards in safeguarding children when fabricated or induced illness (FII) is suspected or proven. The authors identified a lot of uncertainty and anxiety on the part of professionals in managing these situations, and a number of challenges faced by Safeguarding Children Boards.…”
Section: Safeguarding Children When Fabricated or Induced Illness Is Suspected Or Provenmentioning
confidence: 99%
“…I read with interest the paper by Ratcliffe et al (2020) -'Safeguarding children when fabricated or induced illness is suspected or proven: Reviewing the experiences of Local Safeguarding Children Boards in England'.…”
mentioning
confidence: 99%